Linking Theory and Practice in Business Study Process - Lapina, Gundega (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The research paper presents a teaching methodology of Innovation management by using a practical innovation management assessment on-line tool. Empirical study is made with a group of business students, and the results of the research are presented for discussion.The theoretical part of the paper is based on desk research on innovation assessment methods and IMP³rove as one of them. IMP³rove is an on-line assessment and benchmarking platform for a comprehensive assessment of companies’ innovation management. The practical part of the research is focusing on a case study in the RISEBA University. The use of the IMP³rove platform is integrated in the study process. IMP³rove platform is used for academic purposes to link innovation management theory and practice. The latest two years students’ feedback on the IMP³rove assessment method and its usefulness as a learning method are summarized and analyzed, and proposed for discussion and further improvements.